ANALISIS PENENTUAN METODE PERAMALAN PENJUALAN (SALES FORECAST) TERHADAP PENYUSUNAN ANGGARAN PENJUALAN LATEKS PEKAT DAN RUBBER SMOKE SHEET (RSS) PADA PT HUMA INDAH MEKAR TULANG BAWANG - darmajaya, lp4m ibi (Jurnal Manajemen dan Keuangan, 2011)
PT. Huma Indah Mekar (HIM) is one of company focus on processing of pure lateks become thick lateks and rubber smoke sheet. This company is located in Penumangan Baru Village, Central Tulang Bawang, lampung Province. In arrange its budget, PT HIM does not do sales forecast, so there is over budget deviation and caused its not be realistic budget. Problem of this research is started that there is over deviation sales budget (10%). The purpose of this research is deciding of acceptable sales forecast method which is going to be applied at PT Huma Indah Mekar and to arrange sales budget for year 2009. This research methodology is comparative and assosiative with the variable such as sales forecast (dependent variable) and sales budget (independent variable). This research use secondary data taken from marketing data and selling budget for the lateks 5 years (2004-2008). Base on that data, it is made to predict market sell uses least square, method moment, medium average and curve and also is counted by standard deviation of wrong forecast from each method. The result of hypothesis used forecast on marketing year 2009 with moment method and least square to produce think lateksÂ with Y= 4.455.114,8+ 362.745,7 (X) and Y = 5.180.606,2 + 362.745 (X) is Y2009 = 6.268.843 kg with SKP 488.759 the method quadrate linier line. Y= 4.658.237,8 + 362.745,7 (X) + 261.184,2 (X)2 is Y2009= 8.097.132,7 kg with SKP 218.809,84. based on that forecast cause, curve method is more appropriate in apply marketing budget because it has smaller SKP. Selling forecast of rubber smoke sheet Y = 1.100.394-203.015,8 (X) and Y= 694.362,4 - 203.015,8(X) is Y2009 = 85.315 kg with SKP 218.166 whileÂ the curve linear line Y= 830.350,4 â 203.015,8 (X) â 67.994 (X)2 is Y2009 = -390.643 kg with SKP 186.149,25. The arrangement before using marketing forecast, there is over budget deviation more than 10% up to 72,07%, and on the contrary after using this method there is less 10 % deviation 0,6%- 8,35 %. From this statement, it can be concluded that it is not appropriate in determining sales budget which is applied by company. Maksimal kata : 25o kata, abstrak ini : 352 kata Keyword: sales forecase and sales budget.